The democratic backsliding paradigm in enlarged European Union countries: In-depth analysis of V-Dem indicators - Nakai, Ryo (Frontiers in Political Science, 2023)
The phenomena of democratic backsliding in enlarged European Union countries of central, eastern, and southeastern Europe tend to be lumped together. These paradigms fail to capture differences across countries and time, and the differences in backsliding among the subcomponents of liberal democracy. This study analyzes this issue from several indicators provided by V-Dem for 18 countries. The results indicate that democratic backsliding has been occurring in Poland, Hungary, Serbia, and Turkey, while not as much in other countries. What has been observed in these four countries is that the violation of the liberal component of democracy, the weakening of judicial control and restrictions on freedom of expression, comes before the violation of the cleanliness of democracy and the full breakdown of democracy. Through a comparative weighing of multiple indicators, this study clarifies the nuanced reality of democratic regression in the region.